Effect of auricular acupoint embedding therapy combined with health education on relieving insomnia symptoms in patients with chronic gastritis (耳穴埋豆联合健康宣教对慢性胃炎患者失眠症状的改善效果) - ZHENG Weibing (郑伟兵); GUO Xueling (郭雪玲) (Association of Integrative Nursing, 2022)
Objective To explore the effect of auricular acupoint embedding with beans combined with health education on relieving insomnia symptoms in patients with chronic gastritis. Methods Twenty-nine chronic gastritis patients with insomnia were treated with auricular acupoint embedding with beans. The auricular acupoint embedding therapy was performed at auricular acupoints of shenmen, spleen and stomach of unilateral ear, twice a week for two weeks. The health education program was carried out during the treatment. The patients' sleep status was recorded and evaluated using the Pittsburgh Sleep Therapy Index Scale(PSQI). Results After two weeks of treatment, the patient's total PSQI score and dimensional scores (sleep quality, time to sleep, sleep duration, sleep efficiency, sleep disturbance, and daytime dysfunction) improved significantly(P<0. 05). Conclusion Auricular acupoint embedding therapy combined with health education can effectively relieve symptoms of insomnia in patients with chronic gastritis. (目的 探讨耳穴埋豆结合健康宣教对慢性胃炎患者失眠症状的改善效果。方法 选穴神门穴、脾、胃穴, 对29名慢性胃炎伴失眠患者进行单耳轮换耳穴埋豆治疗, 2次/周, 持续两周, 治疗期间配合健康宣教。使用匹兹堡睡眠治疗指数量表(PSQI)记录并评价患者睡眠状态。结果 经过两周治疗后, 患者PSQI总分以及各项PSQI评分(睡眠质量、入睡时间、睡眠时间、睡眠效率、睡眠障碍、日间功能障碍)均明显改善, 差异有统计学意义(P＜0. 01)。结论 耳穴埋豆结合健康宣教的护理方法可以有效改善慢性胃炎患者失眠症状。)